Deciphering Adverse Detrapped Hole Transfer in Hot‐Electron Photoelectric Conversion at Infrared Wavelengths. Issue 12 (12th February 2023) - Yu, Yuanfang; Gao, Lei; Niu, Xianghong; Liu, Kaiyang; Li, Ruizhi; Yang, Dandan; Zeng, Haibo; Wang, Hui‐Qiong; Ni, Zhenhua; Lu, Junpeng
Abstract: Hot‐carrier devices are promising alternatives for enabling path breaking photoelectric conversion. However, existing hot‐carrier devices suffer from low efficiencies, particularly in the infrared region, and ambiguous physical mechanisms. In this work,  the competitive interfacial transfer mechanisms of detrapped holes and hot electrons in hot‐carrier devices are discovered. Through photocurrent polarity research and optical‐pump–THz‐probe (OPTP) spectroscopy, it is verified that detrapped hole transfer (DHT) and hot‐electron transfer (HET) dominate the low‐ and high‐density excitation responses, respectively. The photocurrent ratio assigned to DHT and HET increases from 6.6% to over 1133.3% as the illumination intensity decreases. DHT induces severe degeneration of the external quantum efficiency (EQE), especially at low illumination intensities. The EQE of a hot‐electron device can theoretically increase by over two orders of magnitude at 10 mW cm −2 through DHT elimination. The OPTP results show that competitive transfer arises from the carrier oscillation type and carrier‐density‐related Coulomb screening. The screening intensity determines the excitation weight and hot‐electron cooling scenes and thereby the transfer dynamics. Abstract : Existing hot‐carrier devices suffer from low efficiencies, particularly in the infrared region, and ambiguous physical mechanisms. In this work,  the competitive interfacial transfer mechanisms of detrapped holes and hot electrons in hot‐carrier devices are discovered. By eliminating the adverse detrapped‐hole transfer, the external quantum efficiency of a hot‐electron device can increase by over two orders of magnitude at 10 mW cm −2 .